Modified agreements for the surgeon’s commitment in cosmetic surgeries: an analytical study in Iraqi civil law - Dana Hama Baqi Abdulqadir; Bmo Parwezkhan Al-Dalwi (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The surgeon in Plastic surgery is obliged to perform the operation agreed upon with the patient, and the law permits the amendment of this obligation by mutual agreement the strictness and extenuation of these obligations within the limits of the law. The agreement to amend the obligation varies if focus is given to either element of indebtedness or liability, and it differs according to both forms of amendment (strictness and extenuation) and through this research we focused on the extent of permissibility of the amended agreement on the commitment of the surgeon if the goal of the operation is beautification of the patient, and that depends on the position of the law and the Iraqi judiciary and jurist opinion stated in this regard.